PENDIDIKAN DALAM PERSPEKTIF STRUKTURAL KONFLIK - Binti Maunah (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2015)
This article is to describe education position in the perspective of political conflicts.  Library analysis is used to figure out the description, involving actual and factual references, peer-collaborators and peer-teachers teaching religion education.  A round table discussion is used to finalize the conclusion.  The description involves: (1) education within the conflict structure maintains that each invididual in the classroom has different opinion, needs, and interest arousing conflicts,   (2) conflicts raise both negative and positive views.  Positive conflicts come where sportive competition is involved and enhances students to accomplish fair superiority; in reserve, negative conflicts are destructive, (3) negative conflicts in the classroom may be positive if teachers implements good management conflicts well.